2006
DOI: 10.1080/08860220500530395
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Acute Renal Failure and Factors Predicting Its Outcome in an Intensive Care Unit in India

Abstract: Identification of factors causing acute renal failure (ARF) and its associated poor prognosis in critically ill patients can help in planning strategies to prevent ARF and to prioritize the utilization of sparse and expensive therapeutic modalities. Most of the studies in such patients have been done in the developed world, and similar data from the developing world is sparse. We analyzed 45 consecutive patients who developed ARF in the intensive care unit (ICU) during a 12-month period. Demographic and detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
6
20
0
Order By: Relevance
“…There are many studies that support the relationship between mortality and hypoalbuminemia. [7,8,[11][12][13] Our study also confirms these reports: in our study, mortality was significantly higher in patients with low albumin levels. In future studies, it may be worth investigating the hemodynamic effects of intradialytic or interdialytic albumin infusions in a low-albumin level group.…”
Section: Discussionsupporting
confidence: 82%
“…There are many studies that support the relationship between mortality and hypoalbuminemia. [7,8,[11][12][13] Our study also confirms these reports: in our study, mortality was significantly higher in patients with low albumin levels. In future studies, it may be worth investigating the hemodynamic effects of intradialytic or interdialytic albumin infusions in a low-albumin level group.…”
Section: Discussionsupporting
confidence: 82%
“…[24] A study by Sandeep et al ., which evaluated acute renal failure in ICU, found sepsis to be more common than nephrotoxic drugs. [25] Kaul et al ., in their study have reported acute diarrhea as the most common cause. [26] In our study drug induced AKI accounted for only 5.6% of the cases, which is lower than the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mahajan et al ., who evaluated ARF in ICU, reported that 71.1% required RRT and that intermittent RRT was the most common mode used. [25] These modes are associated with lower cost, lesser adverse effects when compared to the other RRT modes. However, patient outcomes of all three modalities have been shown to be comparable in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in certain regions in Africa and India, boys are more than twice as likely as girls to be taken by their parents to see medical personnel (62)(63)(64)(65)(66). Gender disparity is also expressed in the development of AKI after septic abortion (41,67).…”
Section: Global Perspectivesmentioning
confidence: 99%